2017
DOI: 10.1007/s11099-016-0677-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using smart phones to estimate chlorophyll content in corn plants

Abstract: New spectral absorption photometry methods are introduced to estimate chlorophyll (Chl) content of corn leaves by smart phones. The first method acquires light passing through a leaf by smartphone camera, compensating for differences in illumination conditions. In order to improve performance of the method, spectral absorption photometry (SAP) with background illumination has been considered as well. Data were acquired by smartphone camera in Iowa State University maize fields. Various indices were extracted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 23 publications
2
32
1
Order By: Relevance
“…The coefficient of determination (R 2 ) for the same colour indices in current work (when red LED light passed through leaf) was found to be as 0.3047, 0.8355 and 0.797. The coefficient of determination (R 2 ) of the present study for the linear regression among the R, G and B values with leaf Chl content are also higher than the results of Dey et al (2016), Rigon et al (2016) and Vesali et al (2017). When comparing the Chl a and Chl b in the present study, the estimation of the Chl a was higher than the Chl b.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The coefficient of determination (R 2 ) for the same colour indices in current work (when red LED light passed through leaf) was found to be as 0.3047, 0.8355 and 0.797. The coefficient of determination (R 2 ) of the present study for the linear regression among the R, G and B values with leaf Chl content are also higher than the results of Dey et al (2016), Rigon et al (2016) and Vesali et al (2017). When comparing the Chl a and Chl b in the present study, the estimation of the Chl a was higher than the Chl b.…”
Section: Discussioncontrasting
confidence: 69%
“…Most of the methods used for the determination of the leaf chlorophyll and/or nutrient contents are destructive ones, which are time-consuming and costly (Muñoz-Huerta et al, 2013). Recent studies showed that non-destructive methods (Nicolai et al, 2007) can be used to develop chlorophyll metres, that is, Konica Minolta SPAD-502 ® , for the determination of leaf chlorophyll content and to estimate the nitrogen status of some crops (Scharf et al, 2006;Miao et al, 2009;Vesali et al, 2015;Vesali et al, 2017). Chlorophyll metres use two wavebands, infrared light (at 930 nm) and red light (650 nm) to assess the chlorophyll content (Blackmer et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…They can offer valuable, accurate and rapid information, calculations, measurements, or evaluations of agriculture attributes. Numerous studies have used mobile device applications (apps) to assess green crop cover [ 24 ], ground cover [ 25 ], fractional green canopy cover [ 26 ], turf coverage [ 27 ], leaf area index [ 28 , 29 ], or chlorophyll content in corn plants [ 30 ], or citizen science and/or participatory sensing [ 22 , 31 , 32 ]. One advantage of these devices is that they are equipped with digital cameras and processors, which allow users (i.e., farmers and/or crop advisors) to capture images and perform crop residue analysis efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the smartphone applications in agriculture mainly focus on specific farming activities, such as water and fertilizer calculation, disease detection and diagnosis, pest and weed control, chlorophyll content estimation [28], and tractor-navigation, etc. The available apps which are ready to use include MyPestGuide (), Di@gnoPlant (), WISE (Water Irrigation Scheduling for Efficient Application) [29], Cotton SmartIrrigation App [30], LCFSS (land consolidation field survey system) [31], among others.…”
Section: Improving Als Observation Based On Existing Sensing Technmentioning
confidence: 99%